Nurses’ Knowledge of Pressure Ulcer Risk Assessment and Prevention Strategies: A Cross-Sectional Study in Nigeria - Iyabode Adetoro Gbadamosi; Oluwakemi KOLADE; Patience AMOO (Nursing and Health Sciences Journal (NHSJ), 2023)
The development of PUs consequently results in significant physical, financial, and emotional burdens on the affected patients and their relatives including healthcare providers. This study aimed to assess knowledge of pressure ulcer risk assessment (PURA) and prevention strategies among nurses at University College Hospital (UCH), Ibadan, Nigeria. A cross-sectional descriptive design among 264 nurses was selected through a simple random sampling technique using a structured pre-tested questionnaire for data collection. Data were analyzed using descriptive and inferential statistics. The level of significance is set at a p-value <0.05. The mean age of participants was 40.59 ± 9.88 years. Findings revealed that an average of 51.1% of respondents had adequate knowledge of PURA. However, adequate knowledge of pressure ulcer prevention strategies was recorded among just a little above average 67.8%. Analysis of Variance (ANOVA) showed no significant relationship between respondents’ level of education and their knowledge of pressure ulcer risk assessment as well as their knowledge of pressure ulcer prevention strategies (p>0.05). Knowledge of pressure ulcer and prevention strategies was inadequate. Nurses need regular training programs to improve their knowledge and skills in PURA and the prevention of pressure ulcers among at-risk patients according to international best practices in order to bridge the previously identified gaps.